Financial Market Integration in Pakistan: Evidence Using Post-1999 Data (The Pakistan Development Review, 2006)
The recent wave of financial sector reforms and internationalisation in emerging markets has increased perceived interlinkages within various sectors of national financial markets. For example, the existence of a strong linkage between stock prices and exchange rates is a popular topic in academic research. Similarly, changes in stock prices and exchange rates are expected to influence movements in interest rates. A number of hypotheses suggest such a causal relationship. For instance, using a goods market approach, any changes in the value of currency would affect the competitiveness of multinational firms and hence influence stock prices [Dornbusch and Fischer (1980)]. Similarly, the hypotheses of ‘exchange rate pass-through’ and ‘interest rate pass-through’ suggest that changes in exchange rates and/or interest rates could affect stock prices. The portfolio balance model suggests that fluctuations in stock prices influence exchange rate changes.